More than heavy rain - Johnson, Don, 1942- (Texas Review Press, 2014)
More Than Heavy Rain brings together poems of intense observation culled from a life lived mostly outside. Set mostly around the poet's home along the Watauga River in northeast Tennessee, the poems also reach out to such distant locations as Montana, Alaska, and post-war Germany. Some of them reconstruct the poet's childhood in rural West Virginia. Some examine his family history, the events and relatives who helped determine the way he views the world. LIKE TURNING ON A SWITCHIn a day and a night the leaves of all fourGingko trees in the courty.